UJI PERBANDINGAN BAHAN BAKU BRIKET TERHADAP KUALITAS BRIKET ARANG SHISHA - Rusdianto, Andrew Setiawan; Lathifa, Anisa Millatul; Choiron, Miftahul (Jurnal Penelitian Sains dan Teknologi Indonesia, 2024)
This research was conducted to determine the characteristics of the calorific value, water content, ash content, volatile matter, and combustion rate of each variation of a mixture of quality briquettes and fuel. The research method used was an experimental method with quantitative descriptive data analysis. The selection of the best briquettes is done using the Composite Performance Index (CPI) method. In the research, raw materials with different comparisons were used, namely 60% coconut shell, 60% corn cob, 60% teak wood powder, and 60% sugar cane bagasse. The adhesive used is tapioca flour adhesive at 10% of the weight of the raw material, with a sieve size of 100 mesh and pressure of 100 kg/cm2. The results of this research obtained that the calorific value of all treatments ranged from 5268.51-6009.20 cal/gr, water content ranged from 6.07-6.84%, ash content ranged from 5.69-13.76, volatile matter ranged from 78.54-87.87%, and the burning rate ranged from 0.0176-0.0191%. The CPI value of briquettes with composition from best to lowest in sequence is in treatment P1, namely 100.21, treatment P2, 92.22, treatment P3, 90.94, and treatment P4, namely 86.39.